CO2 Adsorption on Ionic Liquid—Modified Cu-BTC: Experimental and Simulation Study. Issue 2 (February 2015) - Silva, F.W.M. da; Magalhães, G.M.; Jardim, E.O.; Silvestre-Albero, J.; Sepúlveda-Escribano, A.; de Azevedo, D.C.S.; de Lucena, S.M.P.
We analyzed the adsorption of CO2 in a Cu-BTC metal-organic framework (MOF) impregnated with ionic liquids (ILs) experimentally and by molecular simulation using the Monte Carlo method. The ILs [bmim][PF6 ] and [bmim][Tf2 N] were impregnated in concentrations of 1, 5 and 10 wt%. Monte Carlo computations showed maximum impregnation load of approximately 30 wt% and improved CO2 adsorption up to 2 bar for all the concentrations tested. Experimentally, the impregnated material was carefully characterized and CO2 isotherms were measured. High concentrations of IL solution (10 wt%) had a pronounced detrimental effect on the textural properties of Cu-BTC, whereas for low concentration (5 wt%), no improvement in CO2 adsorption was observed. Based on the experimental and simulated data, the suitability of Cu-BTC as a target MOF for IL impregnation was examined.